Mastering identity and access management with Microsoft Azure : start empowering users and protecting corporate data, while managing identities and access with Microsoft Azure in different environments /: start empowering users and protecting corporate data, while managing identities and access with Microsoft Azure in different environments. (2016) - Nickel, Jochen
No abstract available